2010
DOI: 10.4054/demres.2010.23.36
|View full text |Cite
|
Sign up to set email alerts
|

Variations in attitudinal gender preferences for children across 50 less-developed countries

Abstract: While a number of studies have examined gender preferences for children by studying behavioral measures, such as skewed sex ratios, sex imbalance in infant mortality, and sibling size/order; attitudinal measures have been analyzed less systematically. Using 50 Demographic and Health Surveys conducted between 2000 and 2008, this paper seeks to advance our understanding of gender preferences in developing countries by examining attitudinal measures cross-nationally. This study's findings show that, while balance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(87 citation statements)
references
References 21 publications
3
82
0
Order By: Relevance
“…Latin America and the Caribbean (with the exception of Bolivia) along with several Southeast Asian countries showed a predominant daughter preference. Son preference was more prevalent in Southern Asia, Western Asia, and Northern Africa 11 . Individual studies from Egypt, Nepal, and China have reported a strong preference for sons over daughters.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Latin America and the Caribbean (with the exception of Bolivia) along with several Southeast Asian countries showed a predominant daughter preference. Son preference was more prevalent in Southern Asia, Western Asia, and Northern Africa 11 . Individual studies from Egypt, Nepal, and China have reported a strong preference for sons over daughters.…”
Section: Discussionmentioning
confidence: 97%
“…This review demonstrated that son preference was not predominant across countries and daughter preference was common in many countries. 11 Among the countries from South East Asia region a strong preference for sons has been observed in India, China and South Korea. 14 However, the situation regarding son preference in India is alarming, which is frequently associated with the neglect and death of millions of females through infanticide, sex selective abortions, improper nutrition, and lack of medical care 5 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gender preference causes discriminatory practices against children of less-desired sex. Because of the seeming bride price to be earned, female children are often most favoured and better nourished than their male counterparts, resulting in skewed social and health consequences for children (Fuse 2010;Klasen 1996). Mother's working status and household income level have also been examined and found to affect child survival in the developing world (Adebayo and Fahrmeir 2005;Kalipeni 1993) …”
Section: Conceptual Issues Of Child Mortalitymentioning
confidence: 99%
“…Studies on fertility behaviour and contraceptive use have been found to be associated with men's socio-economic status-education and age at marriage (Martinez et al, 2011), marital status (Fuse, 2010), wealth status (Koj, 2000;Hinde and Mturi, 2000), region (Giusti and Vignoli,2006), type of family head, place of residence and religion (Uddin et al, 2011); gender roles (Kaufman 2000;Puur, Oláh et al 2008;Goldscheider et al, 2010), multi-partners (Carlson and Furstenberg 2006;Guzzo and Furstenberg, 2007), income (Guzzo and Furstenberg, 2007) and current number of living children (Lappegård and Rønsen, 2009;Kabagenyi et al, 2014;Kogay and Itua, 2017), among others. Yet, limited studies have delved into men's decision-making role in affecting contraceptive use, as a means of controlling fertility in Nigeria.…”
Section: Introductionmentioning
confidence: 99%